2024
DOI: 10.3390/foods13071094
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Atlantic Mesopelagic Species Processed on Board Commercial Fishing Vessels as a Source of Dietary Lipids

Maria A. Madina,
Eduardo Grimaldo,
Leif Grimsmo
et al.

Abstract: This study investigates the use of untapped mesopelagic species as a source of long-chain polyunsaturated omega-3 fatty acids (LC n-3 PUFAs) to meet the growing demand. The challenges faced by commercial fishing vessels, such as varying catch rates and species distribution affecting lipid levels, are addressed. Marine oils were produced post-catch using thermal separation and enzymatic hydrolysis during four commercial cruises, screening approximately 20,000 kg of mixed mesopelagic species. Maurolicus muelleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Additional studies by Aliyu and colleagues (2022) identified the antioxidant potential of hydrolysates generated from M. muelleri and Krill [3]. More recently, Medina and colleagues looked at on board processing of mesopelagic species including M. muelleri and Benthosema glaciale as a source of dietary lipids [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies by Aliyu and colleagues (2022) identified the antioxidant potential of hydrolysates generated from M. muelleri and Krill [3]. More recently, Medina and colleagues looked at on board processing of mesopelagic species including M. muelleri and Benthosema glaciale as a source of dietary lipids [4].…”
Section: Introductionmentioning
confidence: 99%